Successful management of a Comatose Patient with Traumatic Brain Exposure with a fronto-Parieto-occipital flap - Charles Chidiebele Maduba; Ugochukwu Uzodimma Nnadozie (Journal of Trauma and Injury)
Composite skull defects in patients with severe head injuries are very challenging to manage. The dilemma when deciding whether to perform a definitive reconstruction is how long to wait for physiological recovery before an intervention complicates the situation. The inability of such patients to tolerate prolonged anesthetic exposure is a driving factor for performing the minimal intervention necessary to facilitate recovery. Herein, we present a case involving the successful immediate reconstructive treatment of a severely head-injured adolescent with a composite scalp defect secondary to trauma. A 14-year-old boy sustained a severe head injury from a motor vehicle accident with a composite scalp defect in the right fronto-parietal region. The frontal lobe was exposed, and the right eye was crushed and devitalized. The patient was deeply unconscious for 3 days, without any significant improvements before reconstructive surgery was proposed due to fear of possible meningitis resulting from the exposure of brain structures. We successfully managed the patient with a fronto-parieto-occipital flap, after which the patient promptly recovered consciousness.